Evaluation of Antidiabetic, Renoprotective, and Antioxidant Properties of Aqueous Extracts of Linum usitatissimum in Streptozotocin-Induced Diabetic Rats - Vartika Srivastava; Chaitali Pattanayak; Sougata Sarkar; Mangala Charana Das; Anoushka Prakash (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Introduction: Diabetes is a common metabolic disorder having the phenotype of hyperglycemia. Linum usitatissimum is a blue or purple flowering crop whose consumption has also shown a decrease in postprandial glucose absorption, improvement in glucose tolerance, and serum cholesterol levels. Aim: This study was taken up to evaluate the antiglycemic, renoprotective, and antioxidant effect of various doses of Linum usitatissimum in diabetes so that various long-term complications of the disease could be controlled and minimized. Study Design: The study was conducted for the period of 2 months in the Department of Pharmacology KIMS, Bhubaneswar. A total of 30 albino Wistar rats were taken and divided into five groups containing six rats each. Experimental diabetes was induced in rats by administering a single intraperitoneal injection of streptozotocin in overnight-fasted rats. Group I was diabetic control, Group II was treatment control, and Group III to V rats were given different doses of the extract. Blood samples were taken at the end of 2 months. Results: All the values are expressed as means ± SD. Significant decrease in glycemic parameters, urea, creatinine, and oxidative stress levels were seen at the end of 2 months in all three groups receiving the extract, where the highest dose of extract did maximum reduction, which is comparable with the standard drug. Conclusion: From our study, it can be concluded that there was a significant reduction in glycemic parameters as well as the plant extracts possess excellent renoprotective and antioxidant property, therefore flax seeds are efficient in reducing the long-term complications of diabetes.